Primary amoebic meningoencephalitis in North Queensland: the paediatric experience. Issue 7 (3rd October 2016) - Nicholls, Claire L; Parsonson, Fiona; Gray, Lawrence EK; Heyer, Adele; Donohue, Steven; Wiseman, Greg; Norton, Robert
Summary: Primary amoebic meningoencephalitis (PAM) is a fulminant, diffuse haemorrhagic meningoencephalitis caused by Naegleria fowleri, with an almost invariably fatal outcome. In Australia and the developed world, PAM remains a rare disease, although it is very likely that large numbers of cases go undetected in developing countries. N. fowleri is a thermophilic, free‐living amoeba with a worldwide distribution. It is acquired when contaminated fresh water is flushed into the nose and penetrates the central nervous system via the cribriform plate. Clinical features are similar to those of bacterial meningitis, but it does not respond to standard therapy and rapid progression to death occurs in most cases. Some survivors have been reported; these patients received early treatment with amphotericin B in combination with a variety of other medications. Our review describes the local and worldwide experience of this disease and its clinical features, and discusses the associated diagnostic challenges. We hope that by detailing the local response to a recent case, and the outcomes of our public health campaign, we can improve the knowledge of this rare disease for doctors working in rural and remote Australia.